NDP52 activates nuclear myosin VI to enhance RNA polymerase II transcription. Issue 1 (December 2017) - Fili, Natalia; Hari-Gupta, Yukti; dos Santos, Ália; Cook, Alexander; Poland, Simon; Ameer-Beg, Simon; Parsons, Maddy; Toseland, Christopher
Abstract Myosin VI (MVI) has been found to be overexpressed in ovarian, breast and prostate cancers. Moreover, it has been shown to play a role in regulating cell proliferation and migration, and to interact with RNA Polymerase II (RNAPII). Here, we find that backfolding of MVI regulates its ability to bind DNA and that a putative transcription co-activator NDP52 relieves the auto-inhibition of MVI to enable DNA binding. Additionally, we show that the MVI–NDP52 complex binds RNAPII, which is critical for transcription, and that depletion of NDP52 or MVI reduces steady-state mRNA levels. Lastly, we demonstrate that MVI directly interacts with nuclear receptors to drive expression of target genes, thereby suggesting a link to cell proliferation and migration. Overall, we suggest MVI may function as an auxiliary motor to drive transcription. Myosin VI (MVI) is known to interact with RNA Polymerase II and to play non-cytoplasmic roles in cells. Here, the authors provide evidence that the transcription co-activator NDP52 regulates MVI binding to DNA and that MVI interacts with nuclear receptors to drive gene expression.